Springer handbook of nanotechnology - Bhushan, Bharat 1949- (Gale virtual reference library, 2007)
"A definitive reference book in the nanoscience and nanotechnology area. It integrates the knowledge from nanofabrication, nanodevices, nanomechanics, nanotribology and much more."--Publisher's description.